Collaboration between the Purworejo Regency Government and MDMC in Flood and Landslide Disaster Management - Kaamiliaa Dewi; Herpita Wahyuni; Sakir Sakir (ARISTO, 2026)
This research aims to identify ways to handle flood and landslide disasters in strengthening collaboration between the government and CSOs in Purworejo Regency. Often describe elements of cooperation in handling flood and landslide disasters. The research method applied is qualitative with a case study approach between CSO and the Purworejo Regency Government in disaster management in 2021-2022. The findings of this study show that efficient collaboration in disaster management can be implemented through three important steps, namely: the importance of creating trust between all parties from the beginning, showing a high level of commitment throughout the process, and this collaboration can create common understanding and outcomes that benefit the community and the government. For this reason, the Regional Disaster Management Agency of Purworejo Regency provides a more comprehensive picture of the effectiveness of collaboration in disaster management as well as the factors that contribute to overcoming flood and landslide disasters. However, the implementation of Collaborative Governance has not gone well, this can be seen from the constraints and lack of private sector participation in analyzing articles on flood and landslide disasters. We urgently need input from readers for the development of the next article.